2014
DOI: 10.1016/j.jmatprotec.2013.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Water soluble Invar 36 feedstock development for μPIM

Abstract: Micro powder injection moulding Invar 36 Solid loading optimisationA water soluble binder system based on cellulose acetate butyrate (CAB) and polyethylene glycol (PEG) is proposed and investigated to carry out a micro powder injection moulding (PIM) process with an Invar 36 alloy powders. The overall process was optimised with an emphasis on the determination of the optimal solid loading. Several methodologies were evaluated and compared to determine this parameter. A full PIM was performed with different pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Polyethylene glycol (PEG) is a frequent selection as the water soluble fraction. Hidalgo et al (2014) demonstrated that a solid loading up to 65 vol.% is the most equilibrated choice to successfully fabricate Invar 36 MIM parts with a water-soluble binder system based on cellulose acetate butyrate (CAB) and PEG. The use of solvent soluble waxes can be an alternative to PEG: Zaky at al.…”
Section: Feedstock Composition and Preparationmentioning
confidence: 99%
“…Polyethylene glycol (PEG) is a frequent selection as the water soluble fraction. Hidalgo et al (2014) demonstrated that a solid loading up to 65 vol.% is the most equilibrated choice to successfully fabricate Invar 36 MIM parts with a water-soluble binder system based on cellulose acetate butyrate (CAB) and PEG. The use of solvent soluble waxes can be an alternative to PEG: Zaky at al.…”
Section: Feedstock Composition and Preparationmentioning
confidence: 99%
“…It also displays segregation of the polypropylene. Moreover, the capillary rheology method developed by Hidalgo [5] and Hausnerova [6] was used to characterize the homogeneity of the binder. The results are shown in Fig.…”
Section: Binder Analysismentioning
confidence: 99%
“…Thavanayagan [4] demonstrated the effect of binder properties on the homogeneity of the feedstock. Hidalgo [5] and Hausnerova [6] demonstrated that a capillary rheometer can be used to analyse the homogeneity of the feedstock.…”
Section: Introductionmentioning
confidence: 99%
“…Different methods of water debinding were tested. First the samples are put on a bath of heat water [16,17]. Two different temperatures were tested, 50˝C and 60˝C, and the test were made during 24 h and 48 h because these conditions correspond to removal of the entire PEG from the feedstock made with the PP.…”
Section: Methodsmentioning
confidence: 99%